Cardiac autonomic response following high-intensity running work-to-rest interval manipulation - Cipryan, Lukas; Laursen, Paul B; Plews, Daniel J (European journal of sport science, 2016)
The cardiorespiratory, cardiac autonomic (via heart rate variability (HRV)) and plasma volume responses to varying sequences of high-intensity interval training (HIT) of consistent external work were investigated. Twelve moderately trained males underwent three HIT bouts and one control session. The HIT trials consisted of warm-up, followed by 12 min of 15 s, 30 s or 60 s work:relief HIT sequences at an exercise intensity of 100% of the individual velocity at [Formula: see text]O2max (v[Formula: see text]O2max), interspersed by relief intervals at 60% [Formula: see text]O2max (work/relief ratio = 1). HRV was evaluated via the square root of the mean sum of the squared differences between R-R intervals (rMSSD) before, 1 h, 3 h and 24 h after the exercise. Plasma volume was assessed before, immediately after, and 3 h and 24 h after. There were no substantial between-trial differences in acute cardiorespiratory responses. The rMSSD values remained decreased 1 h after the exercise cessation in all exercise groups. The rMSSD subsequently increased between 1 h and 3 h after exercise, with the most pronounced change in the 15/15 group. There were no relationships between HRV and plasma volume. All HIT protocols resulted in similar cardiorespiratory responses with slightly varying post-exercise HRV responses, with the 30/30 protocol eliciting the least disruption to post-exercise HRV. These post-exercise HRV findings suggest that the 30/30 sequence may be the preferable HIT prescription when the between-training period is limited.
Keywords: Young Adult; Male; Blood Proteins; mladý dospělý; physiology; srdce; Autonomic Nervous System; Cardiorespiratory; Heart Rate; Adult; running; dospělí; mužské pohlaví; srdeční frekvence; Exercise; běh; autonomní nervový systém; krevní proteiny; lidé; Humans; exercise; Running; Heart; cvičení